Analisis Faktor yang Mempengaruhi Harga Beras di Provinsi Papua Menggunakan Regresi Linear Berganda - Kobak, Unyil; Paranoan, Nicea Roona; Aryanto, Aryanto; B, Winda Ade Fitriya (Journal of Health, Education, Economics, Science, and Technology, 2025)
The food security of a country decreases, then the price of staple foods will increase. This price increase can worsen the economic gap and can trigger an increase in poverty rates. Indonesia is one of the countries that has a major food need, namely the need for rice, which is very large. The importance of rice as a staple food and maintaining the stability of rice prices are things that need to be considered. The instability of rice prices can affect the lives of people in a country or region. This study using the price of rice as a response variable and four predictor variables including the farmer's exchange rate, total rice production, and corn prices. The analysis method using multiple linear regression analysis. To see the goodness of the model formed by looking at the coefficient of determination (R2). The results of this study indicate that all research variables do not have a significant effect on influencing the price of rice in Papua Province. The coefficient of determination value obtained from the multiple linear regression model formed is 4.4%.